Characteristics of external loads of Hockey5s associated with the new version of U16 youth field hockey competition - Konarski, J. M.; Andrzejewski, M.; Konefal, M.; Chmura, P.; Skrzypczak, M.; Zahalka, F.; Maly, T.; Malina, R. M. (Scientific Reports, 2023)
External workloads associated Hockey 5 s, the new version of youth field hockey, were evaluated in 31 elite U16 male field players (15.4 ± 0.7 years) from three national teams. Mixed-longitudinal observations for the 31 players provided complete data for 33 forwards and 43 defenders. Activities of the players during games were monitored with the GPSports SPI Elite System with a sampling frequency of 10 Hz and were analysed with GPSports Team AMS (version R1 2015.14, Australia). Observed variables did not differ between forwards and defenders, and the three periods of play were differentiated only by maximal speed in the second and third periods. The greatest distances covered were in speed zone 3 (10.0-15.9 km h-1; 35.5-38.2%) and the smallest in speed zones 4 (16.0-22.9 km h-1; 14.8-15.6%) and 5 (> 23 km h-1; 0.4-1.4%). The trends indicated high intensity levels for the entire match and by position and periods. Active time of forwards and defenders accounted for about one-half of a game`s duration (~ 15.7 of 30 min). Overall, the Hockey 5s format was highly demanding of players and included relatively short intervals for recovery. The results emphasize the need for preparation that includes specific mixed anaerobic and aerobic training and also the importance of recovery during breaks.